Production of laccase and decolourisation of textile dyes by local white-rot fungi / Azlina Hj Md. Kassim @ Hasan - Md. Kassim @ Hasan, Azlina (2007)
A total of 106 local white-rot fungi were screened for their ability to produce the enzyme laccase and to decolourise four textile dyes namely Remazol Brilliant Blue (RBB), Remazol Red (RR), Remazol Yellow (RY) and Procion Yellow (PY). Of these, 22 white-rot fungal isolates were able to produce laccase with activities exceeding 10 U/L. Among these 22 strains, seven decolourised RBB efficiently when cultured on solid media. Isolate UiTM80 was the most efficient decolourising strain and was able to decolourise RBB completely within 6 days. The corresponding laccase production in submerged fermentation reached a maximum of 67 U/L in 5 days. A Plackett-Burman Design and Response Surface Methodology (RSM) were employed to optimise the media for laccase production by UiTM80. Eight parameters were screened for their effects on laccase production; out of which pH and yeast extract were identified as the most significant media components. The RSM study suggested that the optimum media composition for laccase production is as follow: glucose, 10.0 giL; Kl-hP04, 0.50 g/L; trace elements, 5.00 mL/L; yeast extract, 9.83 g/L; ammonium tartarate, 5.24 g/L and pH 7.42. The experimental yield of laccase in this medium was 1,672 ± 950 U/L against a predicted yield of 1,850 U/L. Scale-up studies in a 5 litres-bioreactor showed that 10% inoculum (v/v) of UiTM80 was able to remove 91% of COD and 97% of colour from a 75 ppm RBB dye solution. In industrial textile wastewater, the fungus was able to remove 93% of COD and 33% of colour.